Mapping of ventricular tachycardia in patients with structural heart disease. Issue 4 (9th July 2014) - Mizuno, Hiroya
Abstract: Catheter ablation is now recognized as one of the potent options to reduce the number of implantable cardioverter defibrillator (ICD) shock therapies by modifying arrhythmic substrate in patients affected by ventricular tachycardia (VT). However, operators often face some difficulties during mapping and ablation procedure of VT; unstable VT makes it difficult to create activation map, the thick ventricular myocardium yields complex tachycardia circuit, and endocardial radiofrequency (RF) energy application hardly creates transmural lesion. Thus some novel approaches are required to improve outcome of VT ablation. Substrate mapping aiming low voltage or abnormal fragmented potential could identify the critical slow conduction area during sinus rhythm and define the target of RF delivery. CT and MRI image integrated to electroanatomical mapping (EAM) system also could help to find diseased myocardium. In this article focused on VT mapping procedure, conventional and novel mapping technique as well as some technical tips should be reviewed comprehensively.